Investigation into relationship between procrastinatory behaviour and mathematics achievement of Osun State college of education students (2012)
The study examined academic procrastination in relation to Mathematics academic achievement of Osun State College of Education Students, lla-Orangun. One hundred students taken via census constituted the study sample. An adopted and modified version of a 35-item standardized procrastination scale with r = 0.90 via Cron bach alpha was used for data gathering. Three hypotheses were developed and tested using Pearson Product Moment Correlation; Analysis of Variance [ANOVA], and students-t statistical tools. The result indicated that procrastination had an inverse relationship to and influence on mathematics academic achievement of students and the influence was irrespective of gender. Implication of procrastination on Mathematics achievement was highlighted. And parts of the suggestions for students to overcome procrastination include that; they should find help if needed because staff can usually offer a lot of support and advice if they are confused about a piece of work.